Faktor-Faktor yang Memengaruhi Keputusan Investasi melalui Kebijakan Dividen Sebagai Variabel Mediasi pada Perusahaan Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Jonathan Alexander; Wiwik Fitria Ningsih; Nurshadrina Kartika Sari (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
This study aims to analyze the factors that influence investment decisions by using dividend policy as an intervening variable. The factors referred to in this research are fundamental factors which include profitability, liquidity, leverage, and cash flow. The research uses the path analysis method. The object in this study uses property and real estate companies listed on the Indonesian Stock Exchange during 2017 to 2021. By using the purposive sampling method, there are 16 companies that eventually become samples in this study. The results showed that profitability and cash flow had an effect on dividend policy, while liquidity and leverage had no effect on dividend policy. The results of the analysis of investment decisions show that directly, profitability, cash flow, and dividend policy affect investment decisions, while liquidity and leverage have no effect on investment decisions. Finally, dividend policy is only able to mediate the effect of liquidity and leverage on investment decisions, while dividend policy is not able to mediate the effect of profitability and cash flow on investment decisions.